2015
DOI: 10.1371/journal.pone.0144298
|View full text |Cite|
|
Sign up to set email alerts
|

The Synergistic Local Immunosuppressive Effects of Neural Stem Cells Expressing Indoleamine 2,3-Dioxygenase (IDO) in an Experimental Autoimmune Encephalomyelitis (EAE) Animal Model

Abstract: Neurodegenerative diseases provoke robust immunological reactions in the central nervous system (CNS), which further deteriorate the neural tissue damage. We hypothesized that the expression levels of indoleamine 2,3-dioxygenase (IDO), an enzyme that has potent immune suppressive activities, in neural stem cells (NSCs) would have synergistic therapeutic effects against neurodegenerative diseases, since NSCs themselves have low IDO expression. In this study, the synergistic immune suppressive effects of rat fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Matrigel that was in semiliquid solution at 4°C solidified after in vivo transplantation, which could affect the morphologies of Matrigel. To prepare green fluorescent protein- (GFP-) expressing cells, a lentiviral system (Life Technologies; Carlsbad, CA, USA) was utilized according to previous studies [ 37 , 38 ]. These cell-Matrigel mixtures were transplanted subcutaneously into the dorsal surface of immune-deficient Balb-c/nu mice (6-week-old, male) (Orient Bio; Seongnam, South Korea) under isoflurane (Ifran™, Hana Pharm, Seoul, South Korea) anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Matrigel that was in semiliquid solution at 4°C solidified after in vivo transplantation, which could affect the morphologies of Matrigel. To prepare green fluorescent protein- (GFP-) expressing cells, a lentiviral system (Life Technologies; Carlsbad, CA, USA) was utilized according to previous studies [ 37 , 38 ]. These cell-Matrigel mixtures were transplanted subcutaneously into the dorsal surface of immune-deficient Balb-c/nu mice (6-week-old, male) (Orient Bio; Seongnam, South Korea) under isoflurane (Ifran™, Hana Pharm, Seoul, South Korea) anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“… 2 Interestingly, this study observed no significant impact of IFN-γ exposure on initial KP rate-limiting enzymes, IDO-1/2 or TDO-2. However, our understanding of IDO expression in NSCs remains inconclusive, with alternative studies showing no IDO transcripts or protein in rat foetal NSCs, 306 while the conditionally immortalized CTX0E03 human NSC cell line 307 shows basal IDO-1 expression, which is potently induced by IFN-γ, and IDO-2 and TDO-2 are absent or present in very low abundance in unstimulated and IFN-γ-treated cells. 308 Variation between these studies may be associated with factors including innate differences between primary NSCs and the CTX0E03 cell line, the developmental stage of NSCs (embryonic/foetal versus adult), interspecies variability, or the exposure time and/or concentration of IFN-γ.…”
Section: Stem Cellsmentioning
confidence: 99%
“…Immune suppression is relevant in inflammatory diseases of the CNS such as MS. A study utilising NSCs genetically modified to express high levels of IDO protein, showed IDO-associated inhibition of T cell proliferation in vitro, immune suppression and reduced symptoms when transplanted in EAE-induced mice. 306 An alternative study found that while intravenous injection of IL-10 over-expressing NSCs into EAE mice had an immunosuppressive effect by inhibiting T cell activation; this effect was independent of IDO. 318 The discrepancy in findings may be due to cytokine-specific effects on IDO-linked pathway regulation.…”
Section: Stem Cellsmentioning
confidence: 99%